Assembly of Cerium(III)‐Stabilized Polyoxotungstate Nanoclusters with SeO32−/TeO32− Templates: From Single Polyoxoanions to Inorganic Hollow Spheres in Dilute Solution. Issue 33 (21st June 2013) - Chen, Wei‐Chao; Li, Hao‐Long; Wang, Xin‐Long; Shao, Kui‐Zhan; Su, Zhong‐Min; Wang, En‐Bo
Abstract A versatile one‐pot strategy was employed to synthesize three cerium(III)‐stabilized polyoxotungstates nanoclusters by combining cerium linkers and SeO32−/TeO32− heteroanion templates: K32Na16[(XO3)W10O348Ce8(H2O)20(WO2)4‐ (W4O12)]⋅n H2O [X=Se, n=81 (1); X=Te, n=114 (2)] and K12Na22[(SeO3)W10O348Ce8(H2O)20(WO2)4‐ (W4O6)Ce4(H2O)14(SeO3)4(NO3)2]⋅ 79 H2O (3), which are the first lanthanide‐containing polyoxotungstates with selenium or tellurium heteroatoms. The three clusters were characterized by single‐crystal X‐ray structure analysis, IR spectroscopy, thermogravimetric/differential thermal analysis, UV/Vis spectroscopy, ESI‐MS, and X‐ray photoelectron spectroscopy. Their electrochemical, photoluminescence, and magnetic properties were investigated. Their behavior in solution was studied by transmission electron microscopy, which showed that their single polyoxoanions assemble into intact, uniform‐sized, purely inorganic hollow spheres in dilute water/acetone solution.